Brown recluse (L. rufescens) can bite in Northern Italy, too: first case report and review of the literature. Issue 8 (9th August 2019) - Abbott, David Michael; Brunetti, Enrico; Barruscotti, Stefania; Brazzelli, Valeria
Abstract : The brown recluse, or fiddleback (violin) spider, is a poisonous spider of the Loxosceles genus that resides in warmer regions and old structures making the warm Mediterranean climate a natural habitat for the European species, L. rufescens . Even in infested households, however, bites are rare, as they are nocturnal and unaggressive. In 2015, the first supposed death by L. rufescens occurred in Italy, but before and even after such bite, the literature on these spiders has been under-represented. This case report documents a confirmed bite by a violin spider on a medical student in Pavia, Italy. The presentation in this case was initially with general systemic, flu-like symptoms, then as cellulitis with lymphangitis that persisted for nearly 2 weeks until resolving without prolonged or complicated pathology. We present the first documented case of a L. rufescens bite in Northern Italy, to the best of our knowledge.